LUDWIG'S ANGINA IN PREGNANCY - A RARE CASE REPORT - DR.M.SMITHA,; DR.S.NIRUPA,; DR.K.SARASWATHI, (International Journal of Pharma and Bio Sciences, 2014)
Ludwig’s angina is a very rare and life threatening condition in pregnancy because pregnancy as such is an immunosuppressive state and very few case studies has been reported so far. We present a case report of a 26 years old patient with 20 weeks of gestation admitted with swelling of neck and left side of cheek associated with difficulty in swallowing and opening of mouth, with h/o tooth extraction 9 months back, consistent with Ludwig’s angina. Hence under proper antibiotic coverage and surgical incision and drainage, we successfully relieved her symptoms and under regular followup, she delivered an alive boy baby at 37 weeks of gestation. Postnatal period was uneventful.